Non-pathogenic Neisseria species of the oropharynx as a reservoir of antimicrobial resistance: a cross-sectional study - Gaspari, Valeria; Djusse, Marielle Ezekielle; Morselli, Sara; Rapparini, Luca; Foschi, Claudio; Ambretti, Simone; Lazzarotto, Tiziana; Piraccini, Bianca Maria; Marangoni, Antonella (Frontiers in Cellular and Infection Microbiology, 2023)
Commensal Neisseria species of the oropharynx represent a significant reservoir of antimicrobial resistance determinants that can be transferred to Neisseria gonorrhoeae. This aspect is particularly crucial in ‘men having sex with men’ (MSM), a key population in which pharyngeal co-colonization by N. gonorrhoeae and non-pathogenic Neisseria species is frequent and associated with the emergence of antimicrobial resistance. Here, we explored the antimicrobial susceptibility of a large panel of non-pathogenic Neisseria species isolated from the oropharynx of two populations: a group of MSM attending a ‘sexually transmitted infection’ clinic in Bologna (Italy) (n=108) and a group of males representing a ‘general population’ (n=119). We collected 246 strains, mainly belonging to N. subflava (60%) and N. flavescens (28%) species. Their antimicrobial susceptibility was evaluated assessing the minimum inhibitory concentrations (MICs) for azithromycin, ciprofloxacin, cefotaxime, and ceftriaxone using E-test strips. Overall, commensal Neisseria spp. showed high rates of resistance to azithromycin (90%; median MICs: 4.0 mg/L), and ciprofloxacin (58%; median MICs: 0.12 mg/L), whereas resistance to cephalosporins was far less common (<15%). Neisseria strains from MSM were found to have significantly higher MICs for azithromycin (p=0.0001) and ciprofloxacin (p<0.0001) compared to those from the general population. However, there was no significant difference in cephalosporin MICs between the two groups. The surveillance of the antimicrobial resistance of non-pathogenic Neisseria spp. could be instrumental in predicting the risk of the spread of multi-drug resistant gonorrhea. This information could be an early predictor of an excessive use of antimicrobials, paving the way to innovative screening and prevention policies.